Inferior vena caval tumor thrombus extending into the right atrium in a patient with pancreatic cancer - FAK, ALİ SERDAR; ÖZBEN SADIÇ, BESTE (SPRINGER, 2007)
Venous thromboembolism is a common complication in patients with cancer and an important cause of morbidity and mortality. Idiopathic thrombosis, migratory or recurrent thrombophlebitis may be the first manifestation of an occult malignancy. While deep venous thrombosis and pulmonary embolism are the most common thrombotic conditions in patients with malignant disease, tumor thrombus may be seen in inferior vena cava, mainly in patients with renal cell carcinoma, hepatocellular carcinoma, testicular tumors or adrenal carcinoma. Although pancreatic cancer is one of the cancers that are most strongly associated with thrombotic complications along with cancers of ovary and brain, there has been no report about presence of thrombus in the inferior vena cava in pancreatic cancer. We report a female patient with pancreatic cancer associated with tumor thrombus extending from the inferior vena cava to the right atrium.
Keywords: pancreatic cancer; tumor thrombus; vena caval thrombus; RENAL-CELL CARCINOMA; HEPATOCELLULAR-CARCINOMA; SUCCESSFUL MANAGEMENT; SURGICAL-MANAGEMENT; RISK-FACTORS; RESECTION; EXTENSION; SURGERY; VEIN; ADENOCARCINOMA